Deletion of Sphingosine 1‐Phosphate receptor 1 in cardiomyocytes during development leads to abnormal ventricular conduction and fibrosis. Issue 19 (7th October 2021) - Jorgensen, Ryan; Katta, Meghna; Wolfe, Jayne; Leach, Desiree F.; Lavelle, Bianca; Chun, Jerold; Wilsbacher, Lisa D.
Abstract: Sphingosine 1‐Phosphate receptor 1 (S1P1, encoded by S1pr1 ) is a G protein‐coupled receptor that signals in multiple cell types including endothelial cells and cardiomyocytes. Cardiomyocyte‐specific deletion of S1pr1 during mouse development leads to ventricular noncompaction, with 44% of mutant mice surviving to adulthood. Adult survivors of embryonic cardiomyocyte S1pr1 deletion showed cardiac hypertrabeculation consistent with ventricular noncompaction. Surprisingly, systolic function in mutant mice was preserved through at least 1 year of age. Cardiac conduction was abnormal in cardiomyocyte S1pr1 mutant mice, with prolonged QRS intervals in mutants as compared with littermate control mice. Immunostaining of hearts from S1pr1 mutant embryos displayed a zone of intermediate Connexin 40 (Cx40) expression in the trabecular myocardium. However, we observed no significant differences in Cx40 and Connexin 43 immunostaining in hearts from adult survivors of embryonic cardiomyocyte S1pr1 deletion, which suggests normalized development of the ventricular conduction system in mutant mice. By contrast, the adult survivors of embryonic cardiomyocyte S1pr1 deletion showed increased cardiac fibrosis as compared with littermate controls. These results demonstrate that ventricular hypertrabeculation caused by embryonic deletion of cardiomyocyte S1pr1 correlates with cardiac fibrosis, which contributes to abnormal ventricular conduction. These results also reveal conduction abnormalities in the setting of hypertrabeculation with normal systolic function, which may be of clinical relevance in humans with ventricular hypertrabeculation. Abstract : In adult mice that survived embryonic deletion of S1pr1 in cardiomyocytes, we observed cardiac hypertrabeculation and conduction abnormalities with prolonged QRS. The conduction system marker Connexin 40 (Cx40) displayed an abnormal expression pattern in Mlc2a Cre/+ ; S1pr1 f/− mutant embryos. However, Cx40 and contactin‐2 expression in adult mice did not differ from littermate controls, which suggests normalized development and maintenance of the ventricular conduction system. Finally, cardiomyocyte S1pr1 mutant mice demonstrated increased cardiac fibrosis that correlated with QRS prolongation.